Comparative Validation Study to Demonstrate the Equivalence of an Alternate Next-Day Enrichment Protocol for the TRANSIA® PLATE Salmonella Gold Method to Culture Methods for the Detection of Salmonella in Selected Foods and Environmental Surfaces. (23rd November 2019) - Kerr, David E; Shen, George; Lienau, Andrew H; Deng, Ta; Kaur, Mandeep; Immermann, Amy L; Feldsine, Philip T; John, Lisa; Chen, Yi; Brodsky, Michael; Ziemer, Wayne
Abstract: TRANSIA ® PLATE Salmonella Gold is an ELISA that was validated by Association Française de Normalisation (AFNOR) in 2001 and as a Performance Tested Method SM (PTM) by AOAC in 2006 (PTM No. 010602) as a two-step enrichment protocol requiring 48 h. A simple next-day enrichment protocol using modified Enterohemorrhagic Escherichia coli media was developed for the TRANSIA PLATE Salmonella Gold to improve the time-to-results and laboratory work flow. We tested 128 Salmonella strains, representing all serotypes from A though Z and 51–66. TRANSIA PLATE Salmonella Gold detected all 128 of these strains. None of the 50 non- Salmonella strains were detected by TRANSIA PLATE Salmonella Gold. Performance of TRANSIA PLATE Salmonella Gold using the new enrichment protocol was compared with U.S. Department of Agriculture Microbiology Laboratory Guidebook reference culture procedure for the detection of Salmonella in ready-to-eat poultry, ready-to-eat beef, and chicken carcass rinsate. In addition, TRANSIA PLATE Salmonella Gold performance was compared with U.S. Food and Drug Administration (FDA) Bacteriological Analytical Manual (BAM) for the detection of Salmonella from raw spinach, raw almonds, raw pasta, and environmental surfaces (stainless steel, rubber, and plastic). There was no statistically significant difference in the numbers of positive results TRANSIA PLATE Salmonella Gold protocol compared with the appropriate U.S. Department of Agriculture Food Safety and Inspection Service or FDA-BAM reference methods for any of these matrixes. Robustness testing demonstrated that the introduction of small changes in the normal assay parameters had no impact on the method performance. This new enrichment protocol has been approved as a Third Level modification to Performance Tested Method 010602.